Rapid regional-scale assessments of socio-economic vulnerability to climate change. (7th March 2016) - Smith, Erin F; Lieske, Scott N; Keys, Noni; Smith, Timothy F
Abstract: Assessing socio-economic vulnerability to climate change impacts to support regional decision-making is conceptually and practically challenging. We report on research that tested a rapid assessment approach of socio-economic vulnerability in Australia's natural resource management regions. The approach focuses on regionally important economic sectors, identified using existing datasets, which are likely to be sensitive to climate change impacts. Disaggregated spatial representations of factors known to be associated with vulnerability function as multiple lines of evidence for highlighting intra-regional hotspots of high potential vulnerability. Our results show that a small number of factors based upon contextually relevant empirical evidence offers a low-cost, rapid assessment process, which is readily transferable across regions and provides end-users with guidance for interpreting the results within the context of regional conditions.